2023
DOI: 10.3390/polym15183849
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in Chitosan-Based Nanoparticles for Pulmonary Drug Delivery

Thiago Medeiros Zacaron,
Mariana Leite Simões e Silva,
Mirsiane Pascoal Costa
et al.

Abstract: The evolution of respiratory diseases represents a considerable public health challenge, as they are among the leading causes of death worldwide. In this sense, in addition to the high prevalence of diseases such as asthma, chronic obstructive pulmonary disease, pneumonia, cystic fibrosis, and lung cancer, emerging respiratory diseases, particularly those caused by members of the coronavirus family, have contributed to a significant number of deaths on a global scale over the last two decades. Therefore, sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 163 publications
(241 reference statements)
0
1
0
Order By: Relevance
“…Natural polymers (such as chitosan, sodium alginate, and gelatin) are preferred owing to their superior cytocompatibility and biodegradability. It has been shown that chitosan and alginate enhance nebulization and simplify preparation for pulmonary delivery [94][95][96]. However, natural polymers exhibit certain limitations.…”
Section: Polymeric Npsmentioning
confidence: 99%
“…Natural polymers (such as chitosan, sodium alginate, and gelatin) are preferred owing to their superior cytocompatibility and biodegradability. It has been shown that chitosan and alginate enhance nebulization and simplify preparation for pulmonary delivery [94][95][96]. However, natural polymers exhibit certain limitations.…”
Section: Polymeric Npsmentioning
confidence: 99%
“…It has numerous advantages for vaccine and drug delivery, such as nontoxicity, biocompatibility, biodegradability, strong mucoadhesive properties, and good cost performance [ 9 ]. This LbL trimethylated chitosan-based delivery platform could enhance antigen stability, prolong the duration of action, control drug release, optimize dissolution of poorly soluble peptides, and increase the cell membrane permeability of hydrophobic antigens such as peptides [ 10 ]. Conventional methods for the production of chitosan nanoparticles have been developed in several research groups [ 11 , 12 ], but none of them has been used in the clinic.…”
Section: Introductionmentioning
confidence: 99%